2001
DOI: 10.1177/104063870101300207
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Duration of Porcine Reproductive and Respiratory Syndrome Virus in Semen, Serum, Peripheral Blood Mononuclear Cells, and Tissues from Yorkshire, Hampshire, and Landrace Boars

Abstract: Abstract. Because transmission of porcine reproductive and respiratory syndrome virus (PRRSV) can occur through boar semen, it is important to identify persistently infected boars. However, even for boars given the same PRRSV strain and dose, variability in the duration of viral shedding in semen has been observed, suggesting that host factors are involved in PRRSV persistence. To determine whether there are host genetic factors, particularly litter and breed differences related to the persistence of PRRSV, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 33 publications
3
89
1
2
Order By: Relevance
“…Given the high specificity of the RTnPCR assay demonstrated in this experiment, i.e., 4 false positives among 780 samples from animals known to be PRRS virus negative, these results suggest the detection of inactivated virus in previously infected animals .. Overall, the results of this and previous studies are in agreement: PRRS virus infection results in persistently-infected swine (Allende et al, 2000;Christopher-Hennings et al, 1995;Christopher-Hennings et al, 2001;Wills et al, 1995;Wills et al, 1999). The current study differed from previous studies in that a higher proportion of carriers was detected than previously reported.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Given the high specificity of the RTnPCR assay demonstrated in this experiment, i.e., 4 false positives among 780 samples from animals known to be PRRS virus negative, these results suggest the detection of inactivated virus in previously infected animals .. Overall, the results of this and previous studies are in agreement: PRRS virus infection results in persistently-infected swine (Allende et al, 2000;Christopher-Hennings et al, 1995;Christopher-Hennings et al, 2001;Wills et al, 1995;Wills et al, 1999). The current study differed from previous studies in that a higher proportion of carriers was detected than previously reported.…”
Section: Discussionsupporting
confidence: 81%
“…The detection of PRRS virus in tonsil and/or oropharyngal scrapings has previously been reported (Allende et al, 2000;Benfield et al, 1997;Christopher-Hennings et al, 2001;Wills et al, 1997;Wills et al, 1999). In this study, virus was detected somewhat more frequently in oropharyngeal scraping samples than tonsil tissue samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected animals can shed PRRSV in saliva, nasal secretions, urine, feces, and also in semen. The virus can be shed in semen, even in the absence of viremia and in the presence of neutralizing antibodies [31,32]. This virus most likely reaches the tissues of the reproductive tract and semen by migration of infected monocytes and macrophages [49].…”
Section: Porcine Reproductive and Respiratory Syndrome Virus (Prrsv)mentioning
confidence: 99%
“…4 Landrace, Yorkshire, and Hampshire boars infected experimentally with PRRSV demonstrate variability in the duration of PRRSV seminal shedding among breeds. 3 The observed trend of differences in breed susceptibility to PRRSV-shedding in semen requires further study of variable host factors in PRRSV persistence and resistance. Porcine circovirus type 2 DNA was detected in semen from Duroc and Landrace boars only; however, the semen of the Hamline, Large White maternal, Large White paternal, and Meishan-synthetic boars were negative for PCV2 DNA.…”
mentioning
confidence: 99%